2022
DOI: 10.1097/aud.0000000000001291
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Linked Biology and Gender-Related Research Is Essential to Advancing Hearing Health

Abstract: There is robust evidence that sex (biological) and gender (behavioral/social) differences influence hearing loss risk and outcomes. These differences are noted for animals and humans—in the occurrence of hearing loss, hearing loss progression, and response to interventions. Nevertheless, many studies have not reported or disaggregated data by sex or gender. This article describes the influence of sex-linked biology (specifically sex-linked hormones) and gender on hearing and hearing interventions, including th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 213 publications
0
14
0
Order By: Relevance
“…Although the ovariectomized female mice again demonstrated a similar response to the noise stimulus as the male mice, neither female cohort benefitted from metformin. A lack of otoprotective effects of metformin in female mice may be secondary to insufficient metformin dosing or different metabolism in the female mice (8). Overall, there is a known paucity of clinical trial data regarding the study of disease and effects of medications on women (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the ovariectomized female mice again demonstrated a similar response to the noise stimulus as the male mice, neither female cohort benefitted from metformin. A lack of otoprotective effects of metformin in female mice may be secondary to insufficient metformin dosing or different metabolism in the female mice (8). Overall, there is a known paucity of clinical trial data regarding the study of disease and effects of medications on women (28).…”
Section: Discussionmentioning
confidence: 99%
“…However, to date, the rigorous evaluation of metformin's otoprotective effects against hearing loss in animals of both sexes has not been completed. Furthermore, recent studies demonstrate the importance of hormonal status and biological sex in the susceptibility to NIHL and in the efficacy of potential therapeutics for hearing loss (7,8). In particular, endogenous estrogens are known to have a protective effect on hearing (9).…”
Section: Introductionmentioning
confidence: 99%
“…While the evidence in this study is cross-sectional, we observed specific auditory-cognitive connections in females, this time in a sample of individuals with MCI. Postmenopausal reduction in estrogen, the sex hormone suggested to play a protective role in the inner ear, has downstream negative effects on females’ hearing and likely contributes to the development of their HL (Stenberg et al 2001; Hederstierna et al 2010; Reavis et al 2022). Given the association of menopause with cognitive decline and the development of dementia in females (Mosconi et al 2017), reduction in estrogen may act as a common cause for auditory-cognitive associations in females.…”
Section: Discussionmentioning
confidence: 99%
“…Gender-related factors (e,g., work noise exposure) are known to influence HL (Helzner et al 2005; Palmer et al 2016). Thus, while the current study addressed sex-related differences in auditory-cognitive associations, it is likely that gender also played a role in the observed associations, as sex and gender are strongly intertwined (Reavis et al 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation